Correlation of the hypotonic shock response and extent of shape change with the new ThromboLUX (TM) - Kraemer, L.; Raczat, Tatjana; Weiss, D. R.; Strobel, Joachim; Eckstein, Reinhold; Ringwald, J. (Vox Sanguinis, 2015)
ThromboLUX (TLX)-Score was compared with hypotonic shock response (HSR) and extent of shape change (ESC) in 99 samples from 42 platelet concentrates. Tests were performed in parallel and duplicate. Mean values for TLX Score, HSR and ESC were 30.3 ± 3.8%, 69.0 ± 12.2% and 23.2 ± 4.9%, respectively. We found no significant correlation between TLX Score and HSR or ESC (r = -0.158, P = 0.118 and r = -115, P = 0.255, respectively), whereas HSR and ESC correlated significantly (r = 0.351, P < 0.001). As TLX Score did not show significant correlation with HSR and ESC, the value of TLX for platelet quality testing remains unclear. Studies comparing these parameters with transfusion outcome are needed.
EVALuna2:15993